ANALYSIS OF THE USE OF THE DRILL METHOD IN LEARNING NAHWU IN CLASS 10 IPK 1 MADRASAH ALIYAH AL-ITTIFAQIAH STUDENTS: ANALISIS PENGGUNAAN METODE DRILL DALAM PEMBELAJARAN NAHWU PADA SISWA KELAS 10 IPK 1 MADRASAH ALIYAH AL-ITTIFAQIAH - Dinda Putri Januarita (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2024)
Learning Arabic grammar (Nahwu) remains a significant challenge in Islamic educational institutions, particularly in adapting effective teaching methods that can enhance students' comprehension and practical application of grammatical rules. This study examines the implementation of the Drill method in teaching Nahwu to grade 10 IPK 1 students at Madrasah Aliyah Al-Ittifaqiah. Using a qualitative descriptive approach, this research explores how the Drill method affects students' understanding and mastery of Nahwu principles. Data collection involved participatory observation, in-depth interviews with teachers and students, and documentation analysis over one semester of learning. The findings reveal that systematic implementation of the Drill method significantly improved students' comprehension and ability to apply Nahwu rules. Three key factors influenced the method's effectiveness: teacher competency in designing and executing lessons, student motivation in participating in repeated exercises, and the appropriateness of materials and exercise formats. The study also identified challenges such as student fatigue and individual learning differences, which were addressed through varied exercise formats and differentiated instruction. This research concludes that the Drill method, when properly implemented with appropriate variations and technological integration, serves as an effective strategy for teaching Nahwu at the Madrasah Aliyah level.